PWE-014 Polo-like kinase 1 expression predicts aneuploidy in the Barrett's metaplasia-dysplasia-carcinoma sequence. (28th May 2012) - Butt, M A; Haidry, R J; Oukrif, D; Dunn, J M; Gupta, A; Bhatt, M; Hrynkiewicz, L; Waheed, A; Owen, C; Machhada, A; Rodriguez-Justo, M; Banks, M R; et al.
Abstract : Introduction: Finding an accurate and convenient biomarker for cancer progression in Barrett's (BE) is of high clinical importance. DNA ploidy abnormalities (DNA-PA) are a reliable predictor of cancer risk in BE, but measurement is expensive and scarcely available. We have shown polo-like kinase-1 (PLK1) may act as a surrogate marker of DNA-PA in oesophageal adenocarcinoma (OA) resection specimens. This study aimed to examine the potential of PLK1 in predicting DNA-PA in the metaplasia-dysplasia-OA sequence. Methods: 36 paraffin embedded oesophageal tissue specimens were selected from patients with non-dysplastic BE (NDBE, n=5), low grade dysplasia (LGD, n=5), high grade dysplasia (HGD, n=12), intramucosal cancer (IMC, n=5) and invasive OA (IOA, n=9). Sections were mounted and immunostained with 2 PLK-1 antibodies PLK1-M and PLK1-L using an automated system (BOND-MAX, Leica) for consistency. Results were reported by two independent expert pathologists blinded to patient status with the Allred scoring system, a composite of the percentage and intensity of staining. Results: Aneuploidy was present in LGD (20%), HGD (75%), IMC (20%) and IOA (56%) samples. Using linear regression analysis, Pearson coefficient was calculated for the correlation between DNA-PA and mean Allred expression scores for each PLK1 antibody. PLK1-M had a higher degree of correlation (r 2 =0.26, p=0.001) then PLK1-L (r 2 =0.22, p=0.004). Inter-observer analysis with linear κ scores confirmed good correlation of PLK1-M (κ=0.72, 95% CI 0.60 to 0.83) and PLK1-L (κ=0.53, 95% CI 0.38 to 0.68), but a Bland–Altman plot found pathologist 2 had a trend to score PLK-L more highly. However, intra-observer analysis confirmed both PLK1-L scores correlated with ploidy status (r 2 =0.14, p=0.023 and r 2 =0.27, p=0.0016). Pathologists took 90.3 s/slide (mean) to review and score with the Allred method. Using a mean Allred cut off score of 3.5, the sensitivity and specificity for the detection of aneuploidy were 81.3% and 75% for PLK1-M, 93.8% and 45% for PLK1-L. Conclusion: This pilot study demonstrated a significant correlation between Allred reporting of PLK1 staining and DNA-PA. PLK1-L appears more sensitive and PLK1-M more specific. PLK1 immunostaining is relatively inexpensive, less work intensive and is more available than current methods to predict DNA-PA. Scoring staining with Allred is rapid and reproducible. In future, PLK1 staining may provide the basis of a more durable biomarker panel to predict DNA ploidy. Competing interests: None declared.